The Identification of Metabolites and Effects of Albendazole in Alfalfa (Medicago sativa) - Raisová Stuchlíková, Lucie; Navrátilová, Martina; Langhansová, Lenka; Moťková, Kateřina; Podlipná, Radka; Szotáková, Barbora; Skálová, Lenka (International journal of molecular sciences, 2020)
Albendazole (ABZ), a widely used anthelmintic drug, enters the environment mainly via livestock excrements. To evaluate the environmental impact of ABZ, the knowledge of its uptake, effects and metabolism in all non-target organisms, including plants, is essential. The present study was designed to identify the metabolic pathway of ABZ and to test potential ABZ phytotoxicity in fodder plant alfalfa, with seeds and in vitro regenerants used for these purposes. Alfalfa was chosen, as it may meet manure from ABZ-treated animals in pastures and fields. Alfalfa is often used as a feed of livestock, which might already be infected with helminths. The obtained results showed that ABZ did not inhibit alfalfa seed germination and germ growth, but evoked stress and a toxic effect in alfalfa regenerants. Alfalfa regenerants were able to uptake ABZ and transform it into 21 metabolites. UHPLC-MS/MS analysis revealed three new ABZ metabolites that have not been described yet. The discovery of the parent compound ABZ together with the anthelmintically active and instable metabolites in alfalfa leaves shows that the contact of fodder plants with ABZ-containing manure might represent not only a danger for herbivorous invertebrates, but also may cause the development of ABZ resistance in helminths.
Keywords: anthelmintika; Germination; krmivo pro zvířata; metabolom; Metabolome; Medicago sativa; UHPLC-MS/MS; drugs in the environment; Animal Feed; anthelmintics; albendazol; drug phytotoxicity; Anthelmintics; Albendazole; drug metabolism; klíčení